Plato on the Mechanics of Koinōnia Formation - Stephanides, Stephanos (2022)
This paper argues that, in order to understand the unified relations that are commonly predicated of koinōnia in the ethical, political, and cosmological spheres respectively, one must first appreciate certain prerequisite “principles” or “rules” that are necessary for koinōnia formation. One principle which has been for long the subject of intense discussion in Platonic scholarship is proportionality. However, rather than stopping short at the unproblematically straightforward point of connection between proportionality —in the broadest possible sense— and well-ordered wholes, I suggest that we can get a much richer account from Plato’s preoccupation with proportionality and koinōnia formation by exploring the different proportional models he puts to work in different contexts. It will be argued that for Plato geometrical proportionality in particular is the binding principle par excellence for koinōnia formation as it is the fairest model of order and enables the most enduring complex wholes. Approaching the point from this angle may yet provide a further significant way of understanding the undeniably obvious political differences between the Republic and the Laws in terms of koinōnia formation.